2005
DOI: 10.1074/jbc.m508601200
|View full text |Cite
|
Sign up to set email alerts
|

Role of an S4-S5 Linker Lysine in the Trafficking of the Ca2+-activated K+ Channels IK1 and SK3

Abstract: We have investigated the role of the S4-S5 linker in the trafficking of the intermediate (human (h) IK1) and small (rat SK3) conductance K ؉ channels using a combination of patch-clamp, protein biochemical, and immunofluorescence-based techniques. We demonstrate that a lysine residue (Lys 197 ) located on the intracellular loop between the S4 and S5 domains is necessary for the correct trafficking of hIK1 to the plasma membrane. Mutation of this residue to either alanine or methionine precluded trafficking of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…1A). The internal addition of Tram-34 (1 M) resulted in a near total inhibition of channel activity that was slowly reversible confirming that the Ca 2ϩ -sensitive currents measured under our experimental conditions correspond to KCa3.1 (24,25,44). A series of insideout patch-clamp experiments was next performed to determine whether the KCa3.1 activity could be regulated by AMP.…”
Section: Resultsmentioning
confidence: 99%
“…1A). The internal addition of Tram-34 (1 M) resulted in a near total inhibition of channel activity that was slowly reversible confirming that the Ca 2ϩ -sensitive currents measured under our experimental conditions correspond to KCa3.1 (24,25,44). A series of insideout patch-clamp experiments was next performed to determine whether the KCa3.1 activity could be regulated by AMP.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, specific leucines of the leucine zipper motifs of the C- and N termini of KCa3.1 have been mutated to alanine resulting in altered assembly and trafficking of the channel to the plasma membrane of human epithelial kidney (HEK293) cells (Syme et al, 2003; Jones et al, 2004, 2005). Additionally, Balut et al (2010a), using a novel-tagged channel approach reported, in non-polarized HEK293 cells, that KCa3.1 was endocytosed from the plasma membrane in <90 min and targeted, via a Rab7-ESCRT (endosomal sorting complexes required for transport)-dependent mechanism, for degradation by the lysosome.…”
Section: Introductionmentioning
confidence: 99%
“…Our immunoprecipitations (IP) and immunoblot (IB) protocols have been previously described (28,29,40,41). Briefly, cells were lysed and equivalent amounts of total protein were precleared with protein G-agarose beads (Invitrogen) and incubated with the indicated antibody.…”
Section: Methodsmentioning
confidence: 99%
“…The number of channels in the membrane (N) is regulated by the balance between the anterograde and retrograde trafficking pathways of the channels. Considerable progress has been made in understanding the mechanisms involved in the assembly/trafficking of KCa2.3 and KCa3.1 toward the plasma membrane (18,40,41,51,63); however, the mechanisms of endocytosis and downstream sorting of these channels are virtually unknown. Deciphering the molecular machinery that governs the (post)endocytic trafficking of KCa2.3 and KCa3.1 is the first step in advancing our understanding of how the number of channels is regulated at the plasma membrane, and whether this will result in an altered EDHF response.…”
mentioning
confidence: 99%